Porokeratosis of the scrotum: a case report and literature review - Zhang, Xiaorong; Chen, Bangtao; Yang, Jing (Frontiers in Medicine, 2024)
Porokeratosis, a keratinizing disorder of unknown etiology, exhibits an autosomal dominant inheritance pattern or manifests as an isolated acquired dermatosis. This condition can occur at any site on the skin; however, scrotal lesions are extremely rare. Only 18 cases of scrotal lesions were identified through a comprehensive review of the relevant literature. Herein, we present a case of a 19-year-old patient with porokeratosis of the scrotum. Additionally, we provide a summary of the etiologies, clinical manifestations, and histopathology of scrotal porokeratosis, and present differential diagnoses by reviewing the related literature.